2010
DOI: 10.1002/mrm.22224
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution MRS in the presence of field inhomogeneity via intermolecular double‐quantum coherences on a 3‐T whole‐body scanner

Abstract: Signals from intermolecular double-quantum coherences (iDQCs) have been shown to be insensitive to macroscopic field inhomogeneities and thus enable acquisition of highresolution MR spectroscopy in the presence of large inhomogeneous fields. In this paper, localized iDQC 1 H spectroscopy on a whole-body 3-T MR scanner is reported. Experiments with a brain metabolite phantom were performed to quantify characteristics of the iDQC signal under different conditions. The feasibility of in vivo iDQC high-resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…On the other hand, the methods, e.g. the dynamic nuclear polarization technique [31,32], focusing on improving the sensitivity of NMR experiments may be helpful in promoting the application of HL-IDEAL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the methods, e.g. the dynamic nuclear polarization technique [31,32], focusing on improving the sensitivity of NMR experiments may be helpful in promoting the application of HL-IDEAL.…”
Section: Resultsmentioning
confidence: 99%
“…It has been adopted to localize the iDQC signal on a 3 T whole-body scanner [32]. In this study, the PRESS localization module was adapted to be comprised of three 180 • selective pulses in unison with slice selection gradient and flanked by a pair of spoiling gradients.…”
Section: Theorymentioning
confidence: 99%
“…It is a trade-off for the improvement of spectral resolution under inhomogeneous fields. Also, it has been demonstrated that the sensitivity of high-resolution iMQC spectroscopy is hardly affected by the inhomogeneity under small to moderate inhomogeneous fields (inhomogeneity <1.2 ppm) [16,36]. Several techniques such as dynamic nuclear polarization technique [10,37] have been utilized for iMQC signal intensity improvement.…”
Section: Discussionmentioning
confidence: 99%
“…For example, imaging sequences utilizing DDF have been devised to provide new contrast in magnetic resonance imaging applications, 7,8 to reduce linewidths in magnetic resonance spectroscopy experiments in the presence of large magnetic field inhomogeneities, [9][10][11] for functional MRI studies, 12,13 for brown adipose tissue detection, [14][15][16] and to measure temperature in vivo with high accuracy. 17,18 The main feature of DDF-based sequences is that the DDFderived signal comes primarily from pairs of nuclear spins that are separated by a "correlation distance," a user-controllable distance that can be tuned from a few micrometers to several millimeters, allowing sample structures to be probed at a microscopic scale without the loss of sensitivity.…”
Section: Introductionmentioning
confidence: 99%